Electricity marginal cost pricing applications in eliciting demand responses - Greer, Monica (Butterworth-Heinemann, 2012)
Allows regulators, engineers and energy economists to choose the pricing model that best fits their individual market. This title provides cost issues surrounding the generation, transmission, and distribution of electricity and explains cost models which can yield the marginal cost of supplying electricity to end-users.